Organic Farming Research in India: Present Status and Way Forward - Gopinath, K. A.; Rao, Ch. Srinivasa; Ramanjaneyulu, A. V.; Jayalakshmi, M.; Chary, G. Ravindra; Venkatesh, G. (International Journal of Economic Plants, 2016)
Organic farming is a knowledge intensive system and has been developed by practitioners themselves over the years. Organic farming is native to India. The farmers of ancient India are known to have evolved nature friendly farming systems and practices such as mixed farming, mixed cropping and crop rotation. The first “scientific” approach to organic farming can be quoted back to the Vedas of the “Later Vedic Period”, 1000 BC to 600 BC. There has been significant increase in the area under certified organic farming during the last 10 years. With less than 42,000 ha under certified organic farming during 2003-04, the area under organic farming grew by almost 25 fold, during the next 5 years, to 1.2 million ha during 2008-09. Organic farming is one such system which provides healthy and safe food without ecological harm. Hence, the Government started promoting organic farming through various schemes like National Project on Organic Farming (NPOF), National Horticulture Mission (NHM), Horticulture Mission for North East & Himalayan States (HMNEH), National Project on Management of Soil Health and Fertility (NPMSH&F) and Rashtriya Krishi Vikas Yojana (RKVY). The interest of several States in promoting organic farming indicates that organic agriculture is being viewed as a precursor to dynamic change for an otherwise stagnant agricultural sector. Despite the initiatives and rapid progress, apprehension about the economic viability and environmental and human health benefits of organic farming continue to bother agricultural researchers and policy makers.